2017
DOI: 10.21009/jrmsi.008.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Effect of Profitability, Assets Structure, Size of Companies, and Liquidity to Capital Structures in Mining Companies Listed in Indonesia Stock Exchange Period 2012 - 2015

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 0 publications
3
15
1
6
Order By: Relevance
“…Research that examines the impact of liquidity on capital structure shows a positive effect to capital structure (Arlita, 2019). On the other hand, other studies have shown that liquidity has a significant effect to capital structure (Arilyn, 2020;Salim & Susilowati, 2019;Ahmad et al, 2017). Based on these findings, the fourth hypothesis proposed are: 115 H4: Liquidity effect capital structure in significant relationship.…”
Section: Liquidity (Current Ratio)mentioning
confidence: 89%
See 3 more Smart Citations
“…Research that examines the impact of liquidity on capital structure shows a positive effect to capital structure (Arlita, 2019). On the other hand, other studies have shown that liquidity has a significant effect to capital structure (Arilyn, 2020;Salim & Susilowati, 2019;Ahmad et al, 2017). Based on these findings, the fourth hypothesis proposed are: 115 H4: Liquidity effect capital structure in significant relationship.…”
Section: Liquidity (Current Ratio)mentioning
confidence: 89%
“…Other research results were put forward by Salim & Susilowati in 2019 which stated that profitability, liquidity, assets growth and firm size simultaneously affect the capital structure. Ahmad et al (2017) proves that profitability, asset structure, firm size and liquidity have a simultaneous effect capital structure. Vu et al, 2020 examined the influence of the board size, the board independence, and especially different ownership structures, which include the managerial ownership, the state ownership, the concentrated ownership, and the foreign ownership of the capital structure in Vietnam.…”
Section: A Capital Structurementioning
confidence: 93%
See 2 more Smart Citations
“…The measurement of earnings could be seen through the ratio of Return on Assets (ROA), which was the ability of companies to earn profits with the level of sales of total assets owned and own capital. In this research, the Capital structure is calculated by comparing the total company debt with total equity held by the company and measured using the Debt to Equity Ratio (DER) ratio [3].…”
Section: Introductionmentioning
confidence: 99%